The Notion of Truth in Alain Badiou’s Philosophy: An Analysis of His Conception of Knowledge and Reality (Res Publica. Revista de Historia de las Ideas Políticas, 2023)
The notion of truth has always been the treasure of philosophy, its object of study and debate for centuries. However, nowadays, there are numerous perspectives offering innovative answers to the relationship between truth, knowledge, and reality. Still, none of them shines with overwhelming clarity like Alain Badiou’s philosophy. He not only presents his stance on the debate but also resolves what other perspectives lack. The topic addressed in this article is relevant for at least three reasons. Firstly, by delving into the relationship between truth, knowledge, and reality in Badiou’s work, it revisits a classic territory within the philosophical tradition. Secondly, by posing the problem, it extends beyond the realm of philosophy and engages with current debates in multiple fields, which Badiou refers to as generic procedures of truths. Thirdly, the article seeks to explore the connections between truth and knowledge in Badiou’s philosophy, a topic not commonly studied in the realm of badiousian research.